Economic Survey of the Environmental Horticulture Industry in Florida in 2015 - Alan W. Hodges; Hayk Khachatryan; Mohammad Rahmani; Christa D. Court (EDIS)
"The characteristics and economic contributions of the environmental horticulture industry in Florida in 2015 were evaluated through mail and internet surveys of industry firms conducted in 2016."